By E-Care Pharmacy Web Application, the Medicines Needed for Daily Human Life Can be Easily Delivered to Them - K. A. S, Idushan; P. G. T, Dilshan; K. L. B, Madhushan; P. S, Jayasundera; De Silva, D. I. De Silva; Vidanaarachchi, Samitha (International Journal of Engineering and Management Research, 2022)
This project offers knowledge on creating and putting in place a pharmaceutical management system. And here, the major objective is to increase the efficacy, efficiency, and accuracy of the drug. In today's world, management is one of the most crucial organizational components. Additionally, complexity is added when management does a certain activity in any way. In other words, the availability of computers and advancements in information technology have made it possible for us to swiftly and effectively gather and communicate vast volumes of data on patient treatment. The pharmacy management system should be able to get prescriptions and non-prescription medications with the assistance of certified, trained pharmacists in order to provide patients with the medications they require. Today, many of these types of pharmacy management systems are used to better manage pharmacy-related activities.